Dependence of psychological health of teachers on socio-psychological factors and its theoretical foundations - Tejapova Tillokhon Roziboyevna (Euro Asian Journal Publishing, 2024)
The article describes the causes of the psychological health of teachers, and the modern education system affects all aspects of pedagogical activity: knowledge, pedagogical skills, methods of work, and, of course, teacher's health. opinions are expressed about serious requirements.
Keywords: Professional; teacher; efficiency